An Error Analysis on Writing Recount Text Made by The Eighth Grade Students Of SMPN 3 Sawit Boyolali in 2015/2016 Academic Year - Ardiani, Adhe, Prof. Dr. Endang Fauziati, M. Hum (2016)
The objectives of the study are to describe an error analysis on writing recount text made by eighth grade students of SMP N 3 Sawit Boyolali in their written recount text, identify the types of morphological errors, syntactical errors and discourse errors, describe the frequency type of errors; explain the dominant type of error, identify the source of error and explaining the pedagogical implication to teaching learning English as foreign language. The type of this research is descriptive qualitative research. The researcher uses elicitation technique to collect the data. There are three steps to collect the data, (1) the researcher enter the room class and asks students to write a recount text, the researcher waits the students until finish their works; (2) the researcher collects the data of students writing then reads and marks the types of error that occur in students writing; (3) the researcher documented the erroneous then classifies the type of errors based on linguistic category and surface strategies category. The researcher uses James's theory to classification of error, the researcher uses Slamet's theory to count the frequency of types of error, and the researcher uses the theory from Brown to find the sources of error. The result of the analysis shows that from seventy student's compositional work, there are two hundred and seventy five errors which are grouped into three main categories, namely: morphological error, syntactical error, and discourse error. The highest frequency of errors is wrong spelling of morphological level (33 errors or 12% of errors). The researcher also finds 2 sources of error, namely: interlingual transfer and intralingual transfer. Keywords: error analysis, linguistic category, surface strategy taxonomy, recounts text, source of error.